KAJIAN ADSORPSI ZAT PENGATUR TUMBUH NAPHTHALENE ACETIC ACID (NAA) TERHADAP BENTONIT ALAM - Nura Lailatussoimah; Pedy Artsanti; Irwan Nugraha (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2014)
The study of adsorption of plant growth regulators naphthalene acetic acid (NAA) by using natural bentonite aims to investigate the purification process of bentonite, determine the parameters that affect the ability of optimum adsorption and adsorption interactions of bentonite to NAA. Bentonite purification process is done by adding 30% H2O2 to oxidize organic compounds in the pores of the bentonite. Adsorption parameters in this study include the influence of the mass of adsorbent, contact time and adsorption capacity of bentonite nature of the NAA. Characteristics conducted in this study include analysis using UV-Vis spectrophotometer, infrared spectrophotometry (FTIR) and X-ray Diffraction (XRD). Bentonite adsorption capacity was determined using the model of Langmuir isotherm and Freundlich isotherm models. This study was showed that the amount of NAA more adsorpted by increase the mass of adsorbent in the adsorption process. The optimum contact time between NAA with natural bentonite is 4 hours on the condition of the masses as much as 0.5 grams of bentonite, pH 4.5 and in room temperature (± 29oC) with adsorption capacity of 1.502 × 10-6 mol/g. The optimum adsorption capacity of bentonite to the NAA at 1.712 × 10-6 mol/g. NAA adsorption isotherms with natural bentonite included in the Freundlich adsorption isotherm which assumes the Van der Waals bonds so that the interaction between NAA with bentonite was physically and heterogeneous on the multilayer surface.